Recurrent traumatic hip dislocation in an 8-year-old boy. (April 2021) - Sapage, Rita; Branco, Carlos; Sousa, Rita; Sousa, Diogo; Branco, Ricardo; Lopes, António Lemos
Abstract: Pediatric traumatic hip dislocations (PTHD) are rare and represent around 5% of all pediatric dislocations. Associated bony or soft tissue injury can occur as often as 17%–25% of the time. We report a case of an 8-year-old boy presenting a posterior hip dislocation after a low-energy trauma, which was initially managed with closed reduction and bed rest for 1 week. Two days after hospital discharge, he suffered a recurrent posterior hip dislocation. He was now managed with 4 weeks of bed rest and lower limb skin traction followed by 1 week of no weight-bearing on crutches. With 6 months of follow-up, he is asymptomatic, walking autonomously, with complete and painless range of motion of the affected hip and no major radiographic changes. Pediatric traumatic hip dislocation is a rare and challenging injury that should be managed promptly. Currently, there is no protocol concerning treatment in the literature and its largely dependent of patient and parents' cooperation.